Positive electrode active material, positive electrode including the same, and lithium secondary battery
Patent Information
- Application Number
- JP2024128605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-05
Smart Images

Figure 2025022866000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, and a positive electrode and a lithium secondary battery each containing the positive electrode active material. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, notebook computers, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage power sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been investigated, among which lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, lithium cobalt-based oxides, etc. are mainly used as positive electrode active materials.
[0004] Lithium cobalt oxide can achieve high density in the positive electrode and has excellent high voltage characteristics, but has a problem of insufficient cobalt reserves and high cost. For this reason, there have been attempts to use lithium nickel oxide or lithium manganese oxide, which use elements other than cobalt, as a mixture or as a replacement. However, such positive electrode active materials have disadvantages in that the average voltage obtained is low and the high voltage characteristics are poor. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a positive electrode active material that can reduce the cost of a positive electrode active material including a lithium cobalt-based oxide, but can be driven at a high voltage and can achieve high capacity, high density, and long life. [Means for solving the problem]
[0006] In one embodiment, a positive electrode active material is provided, which includes a first positive electrode active material in a particle form containing a lithium cobalt-based oxide, and a second positive electrode active material in a single particle form that contains a layered lithium nickel-manganese-based composite oxide in which the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, and at least one of the first positive electrode active material and the second positive electrode active material includes a coating layer containing yttrium.
[0007] In another embodiment, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.
[0008] In another embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention
[0009] The positive electrode active material according to an embodiment can improve high voltage characteristics while reducing the cost increase caused by the use of lithium cobalt-based oxide, and can achieve high capacity, high density, and long life characteristics. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 3] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 5] 1 is a scanning electron microscopy (SEM) image of a first positive electrode active material of Preparation Example 1. [Figure 6] 1 is an SEM image of a second positive electrode active material of Preparation Example 5. [Figure 7]1 is an SEM image of small LCO particles of Production Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0015] In the drawings, the thickness of layers and regions is exaggerated to clearly show them, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.
[0016] Here, the term "layer" includes not only shapes formed on the entire surface when observed in a plan view, but also shapes formed on a portion of the surface.
[0017] The average particle size can be measured by methods well known to those skilled in the art, for example, by using a particle size analyzer or a transmission electron microscope image or a scanning electron microscope image. Alternatively, it can be measured using a dynamic light scattering method, and the number of particles in each particle size range can be counted by performing data analysis, and the average particle size value can be calculated from this. Unless otherwise defined, the average particle size is the diameter (D 50 In addition, unless otherwise defined, the average particle size is the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly in a scanning electron microscope image. 50 ) may be taken as the average particle size.
[0018] Here, "or" is not to be construed as exclusive; for example, "A or B" is to be construed as including A, B, A+B, etc.
[0019] The term "metal" is understood to include general metals, transition metals, and metalloids (semimetals).
[0020] positive electrode active material In one embodiment, a positive electrode active material is provided, which includes a first positive electrode active material in the form of particles containing a lithium cobalt-based oxide, and a second positive electrode active material in the form of a single particle, which contains a layered lithium nickel-manganese-based composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of all metals excluding lithium, and at least one of the first positive electrode active material and the second positive electrode active material includes a coating layer containing yttrium. Here, the coating layer means one located on the particle surface of the first positive electrode active material or one located on the single particle surface of the second positive electrode active material. The yttrium coating layer may be present on only one of the first positive electrode active material and the second positive electrode active material, or may be present on both of them.
[0021] Lithium cobalt oxide is widely used in IT batteries due to its excellent high voltage characteristics, single particle morphology, and excellent density characteristics. However, as the price of rare metal cobalt soars, the manufacturing cost of lithium cobalt oxide cathode materials rises, and measures are needed to address this issue. There have been attempts to use high-nickel cathode active materials with reduced cobalt content, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, but these have disadvantages such as a lower average voltage that can be driven compared to lithium cobalt oxide and poor high voltage characteristics. Cobalt-free cathode active materials that do not use cobalt have also been proposed, and among them, cathode active materials with olivine crystal structures such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or spinel crystal structures such as lithium manganese oxide (LMO), have a limited amount of lithium that can be utilized within the structure, limiting their ability to realize high capacity. Layered nickel-manganese positive electrode active materials have a high lithium content in the structure and excellent capacity and efficiency characteristics, making them suitable as materials for high-capacity batteries. However, there are problems with the structural stability and high voltage characteristics being reduced due to the removal of cobalt, which plays a key role in the layered structure.
[0022] In one embodiment, a first positive electrode active material containing a lithium cobalt-based oxide and a second positive electrode active material containing a lithium nickel-manganese-based composite oxide and having a single particle form are mixed, and at least one of the first and second positive electrode active materials is coated with yttrium to reduce the cost of cobalt and improve high voltage characteristics, such as initial discharge capacity and life characteristics at high voltage. The second positive electrode active material according to one embodiment is a layered compound containing nickel and manganese, and has a single particle form, so that it can have a shape similar to that of a lithium cobalt-based oxide. When mixed with the first positive electrode active material, it can achieve a very high positive electrode density and excellent high voltage characteristics. The positive electrode active material according to one embodiment can reduce the cobalt content and improve price competitiveness compared to the case where large and small particles made of lithium cobalt-based oxide are mixed, while achieving a similar level of positive electrode density, and can further improve capacity characteristics and life characteristics at high voltage. In one embodiment, a yttrium coating layer is introduced into at least one of the first and second positive electrode active materials to enhance structural stability and suppress side reactions with the electrolyte, thereby further improving high voltage characteristics.
[0023] The average particle size (D 50 ) is the average particle diameter (D 50 ) may be larger than the particle diameter. In this case, the first positive electrode active material may be expressed as large particles or LCO large particles, and the second positive electrode active material may be expressed as small particles, NM small particles, or NM single particle small particles. LCO means lithium cobalt oxide, and NM means lithium nickel manganese composite oxide. The first positive electrode active material contains lithium cobalt oxide and generally has a single particle form, so the particles of the first positive electrode active material may be expressed as single particles.
[0024] Here, the average particle size (D 50) may be obtained by measuring the sizes (diameter or major axis length) of 20 or more particles randomly selected from a scanning electron microscope image of the positive active material to obtain a particle size distribution, and taking the diameter of the particles that make up 50% of the cumulative volume in the particle size distribution as the average particle size.
[0025] The average particle size (D 50 The average particle diameter (D) of the single particle of the second positive electrode active material may be, for example, 10 μm to 20 μm, 10 μm to 18 μm, or 12 μm to 16 μm. 50 ) can be, for example, 0.5 μm to 8 μm, 1 μm to 7 μm, 1.5 μm to 6 μm, or 2 μm to 5 μm. When the average particle size of each positive electrode active material falls within the above range, high capacity and high energy density can be achieved.
[0026] The first positive electrode active material may be included in an amount of 60% by weight to 95% by weight, for example, 70% by weight to 90% by weight, based on 100% by weight of the total of the first positive electrode active material and the second positive electrode active material. The second positive electrode active material may be included in an amount of 5% by weight to 40% by weight, for example, 10% by weight to 30% by weight, based on 100% by weight of the total of the first positive electrode active material and the second positive electrode active material. When the mixing ratio of the first positive electrode active material and the second positive electrode active material satisfies the above range, the energy density can be increased while maximizing the capacity.
[0027] First positive electrode active material The lithium-cobalt-based oxide of the first positive electrode active material may be represented by, for example, Formula 1 below.
[0028] [Chemical formula 1] Li a1 Co x1 M 1 1-x1 O2 In the formula 1, 0.9≦a1≦1.8 and 0.6≦x1≦1; M 1 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
[0029] In Chemical Formula 1, 0.9≦a1≦1.5, 0.9≦a1≦1.2, or 0.95≦a1≦1.1 may be satisfied. Also, 0.7≦x1≦1, 0.8≦x1≦1, 0.9≦x1≦1, or 0.95≦x1<1 may be satisfied.
[0030] For example, the lithium cobalt-based oxide of the first positive electrode active material may further include aluminum. In this case, aluminum can be considered as a kind of dopant, and M in Formula 1 may be used. 1 When aluminum is doped into lithium cobalt oxide, the capacity and life characteristics at high voltages can be improved.
[0031] The content of aluminum in the lithium cobalt-based oxide may be 1 mol% to 3 mol%, for example, 1.5 mol% to 2.5 mol%, based on 100 mol% of metals excluding lithium in the lithium cobalt-based oxide. When the content of the aluminum dopant satisfies the above range, the high voltage characteristics of the first positive electrode active material may be further improved.
[0032] The first positive electrode active material may include particles containing a lithium-cobalt-based oxide and a coating layer located on the surface of the particles and containing yttrium, aluminum, or a combination thereof. When the coating layer is formed on the first positive electrode active material, the life characteristics or capacity characteristics at high voltage may be further improved.
[0033] When the coating layer contains yttrium, the yttrium content of the coating layer may be 0.01 mol% to 1 mol% based on 100 mol% of the total metals excluding lithium in the first positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.01 mol% to 0.5 mol%, 0.01 mol% to 0.3 mol%, or 0.01 mol% to 0.1 mol%. The yttrium content in the coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the amount of yttrium coating in the first positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity loss.
[0034] When the coating layer contains aluminum, the content of aluminum in the coating layer may be 0.1 mol% to 2 mol% based on 100 mol% of all metals excluding lithium in the first positive electrode active material, for example, 0.1 mol% to 1.5 mol%, 0.1 mol% to 1 mol%, 0.1 mol% to 0.8 mol%, or 0.2 mol% to 0.5 mol%. When the amount of aluminum coating in the first positive electrode active material satisfies the above range, it is possible to improve high voltage characteristics while minimizing capacity loss.
[0035] The thickness of the coating layer of the first positive electrode active material may be 5 nm to 500 nm, for example, 30 nm to 500 nm, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material can be improved and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, through SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and can be measured, for example, through TEM-EDS line profile.
[0036] The coating layer may include both yttrium and aluminum, for example. For example, yttrium may exist in the form of islands in the coating layer, and aluminum may exist in the form of a continuous film.
[0037] Second positive electrode active material The layered lithium nickel-manganese composite oxide of the second positive electrode active material has a nickel content of 60 mol% or more relative to 100 mol% of all metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content is within the above range, a high capacity can be realized, and structural safety can be improved even if the cobalt content is reduced.
[0038] The manganese content may be, for example, 15 mol% or more relative to 100 mol% of all metals excluding lithium in the lithium nickel-manganese based composite oxide, such as 15 mol% to 40 mol%, 15 mol% to 35 mol%, 15 mol% to 30 mol%, or 20 mol% to 30%, etc. When the manganese content satisfies the above range, the positive electrode active material may achieve high capacity while improving structural stability.
[0039] The layered lithium nickel-manganese-based composite oxide may be a lithium nickel-manganese-aluminum-based composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum-based composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the aluminum content satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be achieved.
[0040] The layered lithium nickel-manganese composite oxide can be represented, for example, by the following chemical formula 2.
[0041] [Chemical formula 2] Li a2 Ni x2 Mn y2 Al z2 M 2 w2 O 2-b2 X b2 In the chemical formula 2, 0.9≦a2≦1.8, 0.6≦x2≦0.8, 0.1≦y2≦0.4, 0≦z2≦0.03, 0≦w2≦0.3, 0.9≦x2+y2+z2+w2≦1.1, and 0≦b2≦0.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.
[0042] In Chemical Formula 2, 0.9 ≤ a2 ≤ 1.5, or 0.9 ≤ a2 ≤ 1.2 may hold. Further, Chemical Formula 2 may contain aluminum, and in this case, 0.6 ≤ x2 ≤ 0.8, 0.1 ≤ y2 ≤ 0.39, 0.01 ≤ z2 ≤ 0.03, and 0 ≤ w2 ≤ 0.29 can be satisfied. For example, 0.6 ≤ x2 ≤ 0.8, 0.1 ≤ y2 ≤ 0.39, 0.01 < z2 ≤ 0.03, and 0 ≤ w2 ≤ 0.29 can be satisfied.
[0043] In Chemical Formula 2, for example, 0.6 ≤ x2 ≤ 0.79, 0.6 ≤ x2 ≤ 0.78, 0.6 ≤ x2 ≤ 0.75, 0.65 ≤ x2 ≤ 0.8, or 0.7 ≤ x2 ≤ 0.79 may hold, 0.1 ≤ y2 ≤ 0.35, 0.1 ≤ y2 ≤ 0.30, 0.1 ≤ y2 ≤ 0.29, 0.15 ≤ y2 ≤ 0.39, or 0.2 ≤ y2 ≤ 0.3 may hold, 0.01 ≤ z2 ≤ 0.025, 0.01 < z2 ≤ 0.02, or 0.01 < z2 ≤ 0.019 may hold, and 0 ≤ w2 ≤ 0.28, 0 ≤ w2 ≤ 0.27, 0 ≤ w2 ≤ 0.26, 0 ≤ w2 ≤ 0.25, 0 ≤ w2 ≤ 0.24, 0 ≤ w2 ≤ 0.23, 0 ≤ w2 ≤ 0.22, 0 ≤ w2 ≤ 0.21, 0 ≤ w2 ≤ 0.2, 0 ≤ w2 ≤ 0.15, 0 ≤ w2 ≤ 0.1, or 0 ≤ w2 ≤ 0.09 etc. may hold.
[0044] The layered lithium nickel - manganese - based composite oxide can be a cobalt - free compound that does not contain cobalt or contains a very small amount of cobalt. That is, the content of cobalt with respect to 100 mol% of the total metal excluding lithium in the layered lithium nickel - manganese - based composite oxide can be 0 mol% to 0.01 mol%, or 0 mol% to 0.001 mol%. By applying a second positive electrode active material that contains cobalt or contains a very small amount of cobalt, the manufacturing cost can be reduced, and according to one embodiment, the problem of deterioration of high - voltage characteristics can be effectively prevented.
[0045] The single particle of the second positive electrode active material means a particle that exists alone without a grain boundary and consists of one particle, and may mean a single particle that exists in an independent phase in which the particles do not aggregate with each other in terms of morphology, a monolith structure, a single body structure, or a non-aggregated particle, for example, a single crystal. The single particle may be in a form that is separated alone, or may be in a form where less than 10 single particles are attached to each other.
[0046] The second positive electrode active material may include a coating layer located on the surface of the single particle and containing yttrium, aluminum, or a combination thereof. For example, the second positive electrode active material may include a coating layer containing yttrium, and the coating layer may optionally further include aluminum.
[0047] The yttrium content in the coating layer of the second positive electrode active material may be 0.01 mol% to 1 mol% based on 100 mol% of all metals excluding lithium in the second positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.01 mol% to 0.5 mol%, 0.01 mol% to 0.3 mol%, or 0.01 mol% to 0.1 mol%. The yttrium content in the coating layer may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the amount of yttrium coating in the second positive electrode active material satisfies the above range, it is possible to improve high voltage characteristics while minimizing capacity loss.
[0048] When aluminum is included in the coating layer of the second positive electrode active material, the aluminum content may be 0.1 mol% to 2 mol% based on 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer separately from the aluminum contained inside the single particle. The aluminum content in the coating layer may be measured, for example, through SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, and the resistance of the positive electrode active material is not increased, and side reactions with the electrolyte are effectively suppressed, thereby improving the life characteristics of the lithium secondary battery under high voltage and high temperature conditions.
[0049] The coating layer of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of the single particle, for example, in the form of a shell that surrounds the entire surface of the single particle. This is different from a structure in which only a part of the surface of the particle is partially coated. According to one embodiment, the coating layer may be formed in a form that entirely surrounds the surface of the single particle, but with a very thin and uniform thickness, so that the positive electrode active material has improved structural stability without increasing resistance or decreasing capacity, and side reactions with the electrolyte may be effectively suppressed, thereby achieving long life characteristics at high voltage.
[0050] The thickness of the coating layer of the second positive electrode active material may be 5 nm to 500 nm, for example, 30 nm to 500 nm, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material can be improved and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, through SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and can be measured, for example, through TEM-EDS line profile.
[0051] In the coating layer of the second positive electrode active material, yttrium may exist in the form of islands, and aluminum may exist in the form of a continuous film.
[0052] For example, aluminum and yttrium may be mixed in one coating layer. Alternatively, aluminum and yttrium may form separate layers. For example, the second positive electrode active material may include a first coating layer containing aluminum located on the surface of the single particle, and a second coating layer containing yttrium located on the first coating layer. Aluminum may first be attached or absorbed on the surface of the single particle to form a first coating layer in the form of a thin film, and yttrium may be coated on the first coating layer to form a second coating layer. Of course, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but it can be said that the first coating layer is an aluminum-rich coating layer mainly composed of aluminum, and the second coating layer is an yttrium-rich coating layer mainly composed of yttrium. In this case, yttrium may be present in the second coating layer in the form of islands, but is not particularly limited.
[0053] The thickness of the first coating layer and the second coating layer is not particularly limited, but the thickness of the first coating layer may be 10 nm to 200 nm, for example, 20 nm to 200 nm, 30 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer may be 20 nm to 300 nm, for example, 20 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material is improved, and side reactions with the electrolyte are effectively suppressed to improve life characteristics at high voltage.
[0054] Method for producing positive electrode active material In one embodiment, a method for manufacturing a positive electrode active material is provided, comprising: preparing a first positive electrode active material in the form of particles containing a lithium cobalt-based oxide; preparing a second positive electrode active material in the form of a single particle containing a layered lithium nickel-manganese-based composite oxide in which the nickel content is 60 mol% or more relative to 100 mol% of all metals excluding lithium; and mixing the first positive electrode active material and the second positive electrode active material. Here, at least one of the steps of preparing the first positive electrode active material and the step of preparing the second positive electrode active material includes a step of coating with yttrium. The above-mentioned positive electrode active material can be manufactured through the method.
[0055] For example, the method for preparing the positive electrode active material may include, as a coating process for the first positive electrode active material, mixing an yttrium raw material, an aluminum raw material, or a combination thereof in an aqueous solvent, mixing the mixture with a lithium cobalt-based oxide, and then drying and performing a first heat treatment.
[0056] The yttrium source may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The aluminum source may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. The aqueous solvent may include distilled water, an alcoholic solvent, or a combination thereof.
[0057] When yttrium coating is performed, the yttrium content in the yttrium raw material may be designed to be 0.01 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the first positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.01 mol% to 0.5 mol%, 0.01 mol% to 0.3 mol%, or 0.01 mol% to 0.1 mol%. When the amount of yttrium coating in the first positive electrode active material satisfies the above range, it is possible to improve high voltage characteristics while minimizing capacity loss.
[0058] When aluminum coating is performed, the aluminum content in the aluminum raw material can be designed to be 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the first positive electrode active material, for example, 0.2 mol % to 1.9 mol %, 0.3 mol % to 1.8 mol %, 0.5 mol % to 1.5 mol %, or 0.8 mol % to 1.3 mol %.
[0059] The first heat treatment can be understood as a process of forming a coating layer on the surface of the lithium-cobalt-based oxide particles, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 950°C, 750°C to 950°C, or 800°C to 950°C for 2 hours to 20 hours, or 3 hours to 10 hours.
[0060] For example, the method for preparing the positive electrode active material may include, as a coating process of the second positive electrode active material, mixing an yttrium raw material, an aluminum raw material, or a combination thereof in an aqueous solvent, mixing the single-particle layered type lithium nickel-manganese composite oxide therein, and then drying and performing a second heat treatment.
[0061] Lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has many different surface properties, making it impossible to form a good coating layer with a uniform film shape using existing coating methods. In one embodiment, a method is applied in which a very thin and uniform coating layer is formed on the surface of a layered lithium nickel-manganese composite oxide with a very small cobalt content and a nickel content of 60 mol% or more, thereby improving high voltage characteristics.
[0062] The yttrium source may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The aluminum source may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum source may include aluminum sulfate, and in this case, it is advantageous to form a coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles. The aqueous solvent may include distilled water, an alcoholic solvent, or a combination thereof.
[0063] When yttrium coating is performed, the yttrium content in the yttrium raw material can be designed to be 0.01 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.01 mol% to 0.5 mol%, 0.01 mol% to 0.3 mol%, or 0.01 mol% to 0.1 mol%. When the amount of yttrium coating in the second positive electrode active material satisfies the above range, it is possible to improve high voltage characteristics while minimizing capacity loss.
[0064] When aluminum coating is performed, the aluminum content in the aluminum raw material can be designed to be 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the second positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. By designing the content of the coating raw material within the above range, a coating layer having a thin and uniform thickness of tens to hundreds of nanometers can be formed, and the amount of gas generation of the lithium secondary battery under high voltage driving conditions can be reduced, and high capacity and long life characteristics can be improved.
[0065] The pH of the solution obtained by mixing the yttrium raw material, the aluminum raw material, or a combination thereof in an aqueous solvent may be 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The layered lithium nickel-manganese composite oxide in the form of a single particle may be added thereto and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH value of the mixed solution after stirring may be 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.
[0066] The second heat treatment may be carried out, for example, in an oxygen atmosphere at a temperature range of 700° C. to 850° C., 750° C. to 840° C., or 800° C. to 830° C. for 2 hours to 20 hours, or 3 hours to 10 hours.
[0067] The first and second positive electrode active materials may be mixed in a weight ratio of 60:40 to 95:5, for example, 70:30 to 90:10. When mixed in such a ratio, the energy density can be maximized while improving the capacity and life characteristics.
[0068] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive agent, or a combination thereof.
[0069] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2 ~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.5 g / cc to 3.7 g / cc, for example, 3.5 g / cc to 3.6 g / cc or 3.5 g / cc to 3.58 g / cc. When applying the positive electrode active material according to an embodiment, it is advantageous to realize such a loading level and positive electrode density, and a positive electrode satisfying the loading level and positive electrode density in the above ranges is suitable for realizing a lithium secondary battery with high capacity and high energy density.
[0070] binder The binder serves to adhere the positive electrode active material particles to each other well and to the current collector well. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0071] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Examples of the conductive agent include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0072] The content of the binder and the conductive agent may be 0.5% by weight to 5% by weight, or 0.5% by weight to 3% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.
[0073] The positive electrode current collector may be made of Al, but is not limited to this.
[0074] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive agent, or a combination thereof.
[0075] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material dopable and dedopable with lithium, or a transition metal oxide.
[0076] Examples of the material capable of reversibly inserting / desorbing the lithium ions include carbon-based negative electrode active materials, which can include, for example, crystalline carbon, amorphous carbon, or combinations thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, fired coke, and the like.
[0077] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0078] As the material dopable and dedopable with lithium, an Si negative electrode active material or an Sn-based negative electrode active material can be used. Examples of the Si-based negative electrode active material include silicon, a silicon-carbon composite, SiO x (0 < x < 2), an Si-Q alloy (wherein Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or combinations thereof. Examples of the Sn-based negative electrode active material can be Sn, SnO2, an Sn alloy, or combinations thereof.
[0079] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.
[0080] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0081] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, based on 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, based on 100% by weight of the silicon-carbon composite.
[0082] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50) can be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon can be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.
[0083] The Si-based negative electrode active material or Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are used in combination, the mixing ratio can be 1:99 to 90:10 by weight.
[0084] binder The binder serves to make the negative electrode active material particles adhere well to each other and also make the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.
[0085] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0086] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0087] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.
[0088] The dry binder is a polymeric material capable of being fiberized, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0089] Conductive Agent The conductive agent is used to impart electrical conductivity to the electrode, and any electronically conductive material that does not undergo chemical changes in the battery that is constructed can be used. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0090] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive agent.
[0091] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0092] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.
[0093] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.
[0094] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. As the ether solvent, dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. can be used. As the ketone solvent, cyclohexanone, etc. can be used. As the alcohol solvent, ethyl alcohol, isopropyl alcohol, etc. can be used. As the aprotic solvent, nitriles such as R-CN (R is a straight-chain, branched, or ring-structured hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; sulfolanes, etc. can be used.
[0095] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those working in the field.
[0096] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of 1:1 to 1:9.
[0097] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0098] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.
[0099] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0100] Lithium salts are substances dissolved in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and to facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0101] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.
[0102] < Lithium secondary battery> In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.
[0103] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular type, FIG. 2 shows a square type, and FIGS. 3 and 4 show a pouch type battery. Referring to FIGS. 1 to 4, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). The lithium secondary battery 100 may include a sealing member 60 that seals the case 50 as shown in FIG. 1. Also, the lithium secondary battery 100 in FIG. 2 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.
[0104] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, and may be 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V, etc. By applying the positive electrode active material according to an embodiment, the lithium secondary battery may significantly reduce the amount of gas generated even when charged at a high voltage, and may realize high capacity and long life characteristics.
[0105] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and it is of course possible to use a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator.
[0106] The separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0107] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon, and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.
[0108] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0109] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from a (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.
[0110] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0111] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.
[0112] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.
[0113] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0114] Manufacturing Example 1: Manufacturing of the first positive electrode active material (large LCO particles) The composition is LiCo 0.985 Al 0.015 O2 and the average particle size (D 50A first composite oxide having a particle size of about 18 μm was prepared. Aluminum oxide was added, and the first composite oxide was added thereto and mixed for about 20 to 60 minutes. At this time, the aluminum content in the aluminum oxide was designed to be 0.4 mol % relative to 100 mol % of the total metals excluding lithium in the final first positive electrode active material. This mixture was subjected to a second heat treatment at 950° C. for 8 hours to produce a first positive electrode active material. FIG. 5 is a scanning electron microscope photograph of the produced first positive electrode active material.
[0115] Manufacturing Example 2: Manufacturing of the first positive electrode active material (large LCO particles) The first composite oxide was added with water and yttrium nitrate, coated with yttrium (Y), and then dried. This dried product was mixed with Al2O3 and heat-treated at 950°C for 8 hours to produce a first positive electrode active material in a manner substantially similar to that of Preparation Example 1. Here, the yttrium content in the yttrium nitrate was designed to be 0.05 mol%.
[0116] Manufacturing Example 3: Manufacturing of the first positive electrode active material (large LCO particles) Al, LiCo without Y coating 0.985 Al 0.015 The first composite oxide of O2 was used as the first positive electrode active material.
[0117] The designs of Production Examples 1 to 3 are simply shown in Table 1 below. The capacities and lifetimes in Table 1 were measured by the method of Evaluation Example 1 after manufacturing a positive electrode and a lithium secondary battery as in Example 1 described later, using each of Production Examples 1 to 3 as a positive electrode active material.
[0118] [Table 1]
[0119] Production Example 4: Production of second positive electrode active material (NM small granules) Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated in an oxygen atmosphere at 850℃ for 8 hours to obtain a composition of LiNi 0.75 Mn 0.23 Al0.02 O2 and the average particle size (D 50 A second composite oxide having a single particle shape and a particle size of about 3 μm was produced.
[0120] Aluminum sulfate and yttrium nitrate were mixed into a distilled water solvent, and then the second composite oxide was added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 0.4 mol% based on 100% by weight of the total metals excluding lithium in the final second positive electrode active material, and the yttrium content in the yttrium nitrate was designed to be 0.05 mol%. The solvent was removed from the mixed solution, which was then dried at 190°C and heat-treated in an oxygen atmosphere at 825°C for 8 hours to produce the second positive electrode active material.
[0121] Production Example 5: Production of second positive electrode active material (NM small granules) A second positive electrode active material was prepared in the same manner as in Preparation Example 4, except that the content of yttrium in the yttrium nitrate was designed to be 0.1 mol %. FIG 6 is a scanning electron microscope image of the second positive electrode active material of Preparation Example 5.
[0122] Production Example 6: Production of second positive electrode active material (NM small granules) A second positive electrode active material was prepared in the same manner as in Preparation Example 4, except that yttrium nitrate was not added and only Al coating was performed.
[0123] The designs of Production Examples 4 to 6 are simply shown in Table 2 below. The capacities and lifetimes in Table 2 were measured by the method of Evaluation Example 1 after manufacturing a positive electrode and a lithium secondary battery as in Example 1 described later, using each of Production Examples 4 to 6 as a positive electrode active material.
[0124] [Table 2]
[0125] Production example 7: LCO small grains After mixing aluminum sulfate with distilled water, the average particle size (D 50) is about 4μm 0.98 Al 0.02 O2 particles were added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 0.4 mol% based on 100 mol% of the total metals excluding lithium in the final cathode active material. The solvent was removed from the mixed solution, which was then dried at 190°C and heat-treated at 825°C for 8 hours to produce the cathode active material of Preparation Example 7. Figure 7 is a scanning electron microscope image of the cathode active material of Preparation Example 7 (LCO small particles).
[0126] Production example 8: LCO small grains A positive electrode active material was prepared in substantially the same manner as in Preparation Example 7, except that yttrium nitrate was added together with aluminum sulfate when coating with Al and Y. Here, the content of yttrium in yttrium nitrate was designed to be 0.05 mol% relative to 100 mol% of metals excluding lithium in the final positive electrode material.
[0127] The designs of Preparation Examples 7 and 8 are simply shown in Table 3 below. The capacities and lifetimes in Table 3 were measured by the method of Evaluation Example 1 after applying each of Preparation Examples 7 and 8 as a positive electrode active material and manufacturing a positive electrode and a lithium secondary battery as in Example 1 described later.
[0128] [Table 3]
[0129] Example 1 1. Manufacturing of the positive electrode The first positive electrode active material (LCO large particles) of Preparation Example 1 and the second positive electrode active material (NM small particles) of Preparation Example 4 were mixed in a weight ratio of 8:2 to prepare a positive electrode active material according to Example 1.
[0130] 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive agent were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. The density of the final rolled positive electrode was about 3.52 g / cc.
[0131] 2. Manufacturing of lithium secondary batteries A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.
[0132] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte prepared by dissolving 1M LiPF6 in a solvent containing a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0133] Comparative Example 1 A positive electrode active material, a positive electrode, and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that a mixture of the first positive electrode active material (large LCO particles) of Preparation Example 1 and the second positive electrode active material (small LCO particles) of Preparation Example 7 in a weight ratio of 8:2 was used as the positive electrode active material.
[0134] Evaluation example 1: Evaluation of electrochemical properties and composite density The lithium secondary batteries prepared in Example 1 and Comparative Example 1 were initially charged and discharged at a constant current of 0.2 C to 4.5 V and a constant voltage of 0.05 C at 25° C., and then discharged at 0.2 C to a cut-off voltage of 3.0 V. The initial discharge capacities are shown in Table 4.
[0135] Next, a cycle of charging at 1.0 C and discharging at 1.0 C in a voltage range of 3.0 V to 4.5 V at 45° C. was repeated 50 times or more, and the ratio of the 50 cycle discharge capacity to the initial discharge capacity was calculated. The ratio is shown in Table 4.
[0136] Table 4 shows the densities of the positive electrode composite materials in the rolled state in Example 1 and Comparative Example 1.
[0137] [Table 4]
[0138] Referring to Table 4, Example 1 maintained almost the same positive electrode composite density as Comparative Example 1, while exhibiting improved initial discharge capacity at high voltage and high voltage life characteristics compared to Comparative Example 1.
[0139] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0140] 100: Lithium secondary battery 10: Positive electrode 11: Positive electrode lead tab 12: Positive terminal 20: Negative electrode 21: Negative electrode lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing material 70: Electrode tab 71: Positive electrode tab 72: Negative electrode tab
Claims
1. a first positive electrode active material in the form of particles containing a lithium-cobalt-based oxide; and The second positive electrode active material includes a layered lithium nickel-manganese composite oxide having a nickel content of 60 mol % or more relative to 100 mol % of all metals excluding lithium, and the second positive electrode active material is in the form of a single particle; At least one of the first and second positive electrode active materials includes a coating layer containing yttrium.
2. The average particle size (D 50 ) is the average particle diameter (D 50 2. The positive electrode active material of claim 1 , wherein the positive electrode active material has a capacitance greater than 100%.
3. The average particle size (D 50 ) is 10 μm to 20 μm, The average particle diameter (D 50 2. The positive electrode active material according to claim 1, wherein the thickness of the first electrode is 0.5 μm to 8 μm.
4. 2. The positive electrode active material according to claim 1, wherein the first positive electrode active material is contained in an amount of 60% by weight to 95% by weight, and the second positive electrode active material is contained in an amount of 5% by weight to 40% by weight, relative to a total weight of 100% by weight of the first positive electrode active material and the second positive electrode active material.
5. The positive electrode active material according to claim 1 , wherein the first positive electrode active material is a lithium-cobalt-based oxide represented by Chemical Formula 1: [Chemical formula 1] Li a1 Co x1 M 1 1-x1 O 2 (In the above formula 1, 0.9≦a1≦1.8, 0.6≦x1≦1, and M 1 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.
6. The lithium-cobalt-based oxide of the first positive electrode active material further contains aluminum, 2. The positive electrode active material according to claim 1, wherein the content of aluminum in the lithium-cobalt-based oxide is 1 mol % to 3 mol % relative to 100 mol % of metals excluding lithium.
7. 10. The cathode active material of claim 1, wherein the first cathode active material comprises particles containing a lithium cobalt-based oxide and a coating layer located on a surface of the particles and containing yttrium, aluminum, or a combination thereof.
8. 8. The positive electrode active material of claim 7, wherein the coating layer contains yttrium, and the yttrium content of the coating layer is 0.01 mol % to 1 mol % based on 100 mol % of all metals excluding lithium in the first positive electrode active material.
9. 8. The positive electrode active material of claim 7, wherein the coating layer comprises aluminum, and the aluminum content of the coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the first positive electrode active material.
10. The cathode active material of claim 7, wherein the coating layer of the first cathode active material has a thickness of 5 nm to 500 nm.
11. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the second positive electrode active material has a nickel content of 60 mol% to 80 mol% and a manganese content of 15 mol% or more relative to 100 mol% of all metals excluding lithium.
12. The layered lithium nickel-manganese composite oxide of the second positive electrode active material further contains aluminum, and the content of aluminum in the layered lithium nickel-manganese composite oxide is 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to claim 1.
13. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the second positive electrode active material has a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.
14. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the second positive electrode active material is represented by chemical formula 2. [Chemical formula 2] Li a2 Ni x2 Mn y2 Al z2 M 2 w2 O 2-b2 X b2 (In Chemical Formula 2, 0.9≦a2≦1.8, 0.6≦x2≦0.8, 0.1≦y2≦0.4, 0≦z2≦0.03, 0≦w2≦0.3, 0.9≦x2+y2+z2+w2≦1.1, and 0≦b2≦0.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.
15. 10. The cathode active material of claim 1, wherein the second cathode active material comprises a coating layer located on a surface of the single particle and containing yttrium, aluminum, or a combination thereof.
16. 16. The positive electrode active material of claim 15, wherein the coating layer contains yttrium, and the yttrium content of the coating layer is 0.01 mol % to 1 mol % based on 100 mol % of all metals excluding lithium in the second positive electrode active material.
17. 16. The positive electrode active material of claim 15, wherein the coating layer comprises aluminum, and the aluminum content of the coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the second positive electrode active material.
18. The cathode active material according to claim 15, wherein the coating layer of the second cathode active material has a thickness of 5 nm to 500 nm.
19. 16. The positive electrode active material of claim 15, wherein the coating layer of the second positive electrode active material contains both yttrium and aluminum, and in the coating layer, yttrium is present in the form of islands and aluminum is present in the form of a continuous film.
20. 16. The cathode active material of claim 15, wherein the second cathode active material comprises a first coating layer located on a surface of the single particle and containing aluminum, and a second coating layer located on the first coating layer and containing yttrium.
21. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 20.
22. 22. The positive electrode of claim 21, wherein the positive electrode active material layer has a density of 3.5 g / cc to 3.7 g / cc.
23. The positive electrode according to claim 21 . a negative electrode, and A lithium secondary battery containing an electrolyte.
24. The lithium secondary battery according to claim 23, having a charging voltage of 4.45 V or higher.
Citation Information
Patent Citations
High-performance positive pole piece as well as preparation method and application thereof
CN115863529A
Cathode active material, manufacturing method of the same, and battery
JP2007066839A
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2012169289A
Positive electrode active material, positive electrode and lithium battery including the positive electrode active material, and method of manufacturing the positive electrode active material
JP2015149275A
Smart table ordering apparatus of providing vehicle call function and sterilization function and operating method thereof
KR1020250006451A